2009
DOI: 10.1186/1475-2875-8-s2-s4
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation and mass rearing: learning from others

Abstract: Mosquitoes, just as other insects produced for the sterile insect technique (SIT), are subjected to several unnatural processes including laboratory colonisation and large-scale factory production. After these processes, sterile male mosquitoes must perform the natural task of locating and mating with wild females. Therefore, the colonisation and production processes must preserve characters necessary for these functions. Fortunately, in contrast to natural selection which favours a suite of characteristics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
126
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 38 publications
1
126
0
1
Order By: Relevance
“…However, Dao et al (2008) showed that when both species congregate inside huts, cross-species mating is as frequent as within-species mating, indicating that assortative mating breaks down when mating occurs indoors. This is consistent with reports observing the absence of assortative mating in lab-reared Anopheles colonies (Benedict et al, 2009;Paton et al, 2013), which, overall, suggests that chemical cues such as pheromones and cuticular hydrocarbons (Dao et al, 2008) and flight tones (Dao et al, 2008;Tripet et al, 2004) do not play a major role in species recognition. Data are given as the range and/or mean±s.e.m.…”
Section: Discussionsupporting
confidence: 80%
“…However, Dao et al (2008) showed that when both species congregate inside huts, cross-species mating is as frequent as within-species mating, indicating that assortative mating breaks down when mating occurs indoors. This is consistent with reports observing the absence of assortative mating in lab-reared Anopheles colonies (Benedict et al, 2009;Paton et al, 2013), which, overall, suggests that chemical cues such as pheromones and cuticular hydrocarbons (Dao et al, 2008) and flight tones (Dao et al, 2008;Tripet et al, 2004) do not play a major role in species recognition. Data are given as the range and/or mean±s.e.m.…”
Section: Discussionsupporting
confidence: 80%
“…aegypti (and other mosquito species) there is a significant size difference between the male and female pupae which can be exploited for sex separation techniques. The sorted RIDL males are then released in a control program as either pupae or as adults 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…albopictus ADAM approach will require large-scale production, i.e., 'mass rearing,' of mosquitoes for release. This type of mass rearing operation is developed already and in use with other autocidal approaches, including Sterile Insect Technique (SIT) [47][48][49]. Furthermore, the potential benefit of PPF treatment to 'boosting' autocidal approaches has been highlighted previously [50].…”
Section: Discussionmentioning
confidence: 99%